Terror on the train - Dams, Jeanne M. (Dams, Jeanne M. Dorothy Martin mysteries, 2025)
"Dorothy Martin and her husband, retired chief constable Alan Nesbitt, are leaving England behind to attend a wedding on Vancouver Island, Canada. Opting for the scenic route, the pair board the Empire Builder sleeper train from Chicago to Seattle. But the journey takes a terrifying turn when Dorothy witnesses a person falling from the train. The body of a man is quickly found on the route, and Dorothy feels compelled to investigate. Who was he? Was he alive or dead when he fell? Could his fate be linked to a confrontation on the train? As Dorothy and Alan unravel the secrets surrounding the dead man, they uncover disturbingly dark truths ..."--